2022
DOI: 10.1108/ijse-06-2022-0420
|View full text |Cite
|
Sign up to set email alerts
|

Investigating drivers of qardhul hassan financing acceptance in the time of COVID-19: a Malaysian breadwinner perspective

Abstract: PurposeThis study was conducted to examine factors that could determine breadwinners' willingness to accept qardhul hassan financing in the time of coronavirus disease 2019 (COVID-19).Design/methodology/approachDrawing upon ‘Attitude, Social Influence and Self-Efficacy’ (ASE) model, this study examined the effects of attitude, subjective influence and self-efficacy on qardhul hassan financing acceptance during the pandemic. The sample size was 294 respondents who were all breadwinners and sourced from group bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…Zakah or shadaqah institution can use QH to help the poor. QH is increasingly showing its role during the covid pandemic where many people need help to fulfil their needs (Amin, 2022). Zakah institutions in Indonesia can be divided into two types: amil zakah institutions – established by private organisations, and the National Board of Amil Zakah – established by the government.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zakah or shadaqah institution can use QH to help the poor. QH is increasingly showing its role during the covid pandemic where many people need help to fulfil their needs (Amin, 2022). Zakah institutions in Indonesia can be divided into two types: amil zakah institutions – established by private organisations, and the National Board of Amil Zakah – established by the government.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shed light on the role of QH financing in the economy. Amin (2022) stated that QH financing is urgently needed by Malaysian breadwinners as a beneficial financial assistance, especially during the COVID-19 period. Unstable financial conditions during the pandemic have further strengthened QH’s role as a facility that can help meet their needs, such as food, emergency, education and business capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…IBs are expected to consider social engagement and not only focus on profit (Chapra, 1979;Ahmad, 2000;Al-Zuhayli, 2003;Hamidi and Worthington, 2023). The Shariah in principle encourages IBs to engage in social financing to assist low-income earners such as the farmers using bai'salam contracts, financing Small and Medium Scale Enterprises (SMEs) through sadaqat and musharakah, providing soft loans using qard al-hasan, extending charitable means and paying zakat (Dasuki, 2008;Hassan and Harahap, 2010;Abd Samad et al, 2018;Amin, 2022b). These variables are seen as social finance instruments (Bani et al, 2015).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Within the realm of consumer behavior, the inclination to acquire a product is predicated upon a favorable disposition toward the said product, with the potential for attitudes toward alternative products within the available options also exerting an influence on this positive disposition (Laroche et al, 1996). Significantly, scholarly research in the field of Islamic finance has placed considerable emphasis on the significance of attitude as a crucial determinant in shaping the intention to utilize Islamic personal financing, as highlighted by Amin et al (2010). Moreover, previous research has indicated that individuals with a positive attitude or a favorable inclination toward Islamic financing exhibit a greater intention to obtain Islamic personal financing products (Fauziah et al, 2008;Ahmed et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%